Transcriptome Profiling Insights the Feature of Sex Reversal Induced by High Temperature in Tongue Sole Cynoglossus semilaevis - Liu, Jinxiang; Liu, Xiaobing; Jin, Chaofan; Du, Xinxin; He, Yan; Zhang, Quanqi (Frontiers in Genetics, 2019)
Sex reversal induced by temperature change is a common feature in fish. Usually, the sex ratio shift occurs when temperature deviates too much from normal during embryogenesis or sex differentiation stages. Despite decades of work, the mechanism of how temperature functions during early development and sex reversal remains mysterious. In this study, we used Chinese tongue sole as a model to identify features from gonad transcriptomic and epigenetic mechanisms involved in temperature induced masculinization. Some of genetic females reversed to pseudomales after high temperature treatment which caused the sex ratio imbalance. RNA-seq data showed that the expression profiles of females and males were significantly different, and set of genes showed sexually dimorphic expression. The general transcriptomic feature of pesudomales was similar with males, but the genes involved in spermatogenesis and energy metabolism were differentially expressed. In gonads, the methylation level of cyp19a1a promoter was higher in females than in males and pseudomales. Furthermore, high-temperature treatment increased the cyp19a1a promoter methylation levels of females. We observed a significant negative correlation between methylation levels and expression of cyp19ala. In vitro study showed that CpG within the cAMP response element (CRE) of the cyp19a1a promoter was hypermethylated, and DNA methylation decreased the basal and forskolin-induced activities of cyp19a1a promoter. These results suggested that epigenetic change, i.e., DNA methylation, which regulate the expression of cyp19a1a might be the mechanism for the temperature induced masculinization in tongue sole. It may be a common mechanism in teleost that can be induced sex reversal by temperature.